momHealth: A Feasibility Study of a Multi-behavioral Health Intervention for Pregnant and Parenting Adolescent Mothers - Wambach, Karen; Davis, Ann; Nelson, Eve Lynn; Snow, Kelli; Yungmeyer, Annie; Muzzy, Rachel; Romero, Karman; Murray, Megan (Kansas Journal of Medicine, 2021)
Introduction. In 2016, 209,809 babies were born to mothers 15 -19 years of age, for a live birth rate of 20.3 per 1,000 in this age group. Many health issues surround adolescent mothers and their infants, many which can be addressed through behavioral change. We examined feasibility and acceptability of momHealth, a Multiple Health Behavior Change (MHBC) intervention focused on breastfeeding, healthy eating/active living, and depression prevention among pregnant and parenting adolescents. Methods. We used a one-group quasi-experimental longitudinal design. Nine iPad-delivered education modules, text messaging, and virtual group and individual support were provided for 12 weeks, beginning at 32 weeks of pregnancy with follow-up to 3 months postpartum. Data were collected at three home visits and ten postpartum weekly and biweekly online surveys. Results. Although recruitment and attrition presented challenges, six participants enrolled; all were pregnant with their first child, single, and had a mean age of 17.7 years (SD = 1.4). Intervention participation ranged from 59% to 91% for intervention components and three peer support groups were held. Intervention feasibility was supported by reports of clear and relevant content, reasonable time burden, iPad ease of use, and acceptable intervention length. Data collection was reported as convenient and non-burdensome, but diet recalls and activity monitoring challenged some. Conclusions. This was the first MHBC research in adolescent pregnant women to improve breastfeeding outcomes, healthy eating/active living, and depression prevention. Findings demonstrated strengths and challenges of the interventions and methods, support feasibility and acceptability of momhealth, and informed a pilot randomized trial.